Revision of the genus Jezarotes Uchida (Hymenoptera: Ichneumonidae: Acaenitinae), with the description of a new species from Laos - Ito, Masato; Maeto, Kaoru (Zootaxa, 2015)
Two Japanese species of Jezarotes, J. tamanukii Uchida, 1928, and J. yamatonis Uchida, 1928, are synonymized based on the results of a morphological examination and DNA sequence analysis of the mitochondrial COI gene. Jezarotes tetragonis Lee & Lee, 2009, from Korea is also synonymized with J. tamanukii. The key to the world’s species of Jezarotes proposed by Lee & Lee (2009) is updated, including a new species J. mitai sp. nov. from Laos.